The Use of Pointwise Encoding Time Reduction With Radial Acquisition MRA to Assess Middle Cerebral Artery Stenosis Pre- and Post-stent Angioplasty: Comparison With 3D Time-of-Flight MRA and DSA - Zhang, Feifei; Ran, Yuncai; Zhu, Ming; Lei, Xiaowen; Niu, Junxia; Wang, Xiao; Zhang, Yong; Li, Shujian; Zhu, Jinxia; Gao, Xuemei; Mossa-Basha, Mahmud; Cheng, Jingliang; et al. (Frontiers in Cardiovascular Medicine, 2021)
BACKGROUND AND PURPOSE: 3D pointwise encoding time reduction MR angiography (PETRA-MRA) is a promising non-contrast MRA technique for intracranial stenosis assessment but it has not been adequately validated against digital subtraction angiography (DSA) relative to 3D-time-of-flight (3D-TOF) MRA. The aim of this study was to compare PETRA-MRA and 3D-TOF-MRA using DSA as the reference standard for intracranial stenosis assessment before and after angioplasty and stenting in patients with middle cerebral artery (MCA) stenosis. MATERIALS AND METHODS: 62 patients with MCA stenosis (age 53±12 years, 43 males) underwent MRA and DSA within a week for pre-intervention evaluation and 32 of them had intracranial angioplasty and stenting performed. The MRAs' image quality, flow visualization within the stents, and susceptibility artifact were graded on a 1-4 scale (1=poor, 4=excellent) independently by three radiologists. The degree of stenosis was measured by two radiologists independently on DSA and MRAs. RESULTS: There was an excellent inter-observer agreement for stenosis assessment on PETRA-MRA, 3D-TOF-MRA, and DSA (ICCs>0.90). For pre-intervention evaluation, PETRA-MRA had better image quality than 3D-TOF-MRA (3.87±0.34 vs. 3.38±0.65, P<0.001), and PETRA-MRA had better agreement with DSA for stenosis measurements compared to 3D-TOF-MRA (r=0.96 vs. r=0.85). For post-intervention evaluation, PETRA-MRA had better image quality than 3D-TOF-MRA for in-stent flow visualization and susceptibility artifacts (3.34±0.60 vs. 1.50±0.76, P<0.001; 3.31±0.64 vs. 1.41±0.61, P<0.001, respectively), and better agreement with DSA for stenosis measurements than 3D-TOF-MRA (r=0.90 vs. r=0.26). 3D-TOF-MRA significantly overestimated the stenosis post-stenting compared to DSA (84.9%±19.7% vs. 39.3%±13.6%, p<0.001) while PETRA-MRA didn’t (40.6%±13.7% vs. 39.3%±13.6%, p=0.18). CONCLUSIONS: PETRA-MRA is accurate and reproducible for quantifying MCA stenosis both pre-and post-stenting compared with DSA and performs better than 3D-TOF-MRA.